The AaCBF4-AaBAM3.1 module enhances freezing tolerance of kiwifruit (Actinidia arguta). (1st May 2021) - Sun, Shihang; Hu, Chungen; Qi, Xiujuan; Chen, Jinyong; Zhong, Yunpeng; Muhammad, Abid; Lin, Miaomiao; Fang, Jinbao
Abstract: Beta-amylase (BAM) plays an important role in plant resistance to cold stress. However, the specific role of the BAM gene in freezing tolerance is poorly understood. In this study, we demonstrated that a cold-responsive gene module was involved in the freezing tolerance of kiwifruit. In this module, the expression of AaBAM3.1, which encodes a functional protein, was induced by cold stress. AaBAM3.1 -overexpressing kiwifruit lines showed increased freezing tolerance, and the heterologous overexpression of AaBAM3.1 in Arabidopsis thaliana resulted in a similar phenotype. The results of promoter GUS activity and cis -element analyses predicted AaCBF4 to be an upstream transcription factor that could regulate AaBAM3.1 expression. Further investigation of protein-DNA interactions by using yeast one-hybrid, GUS coexpression, and dual luciferase reporter assays confirmed that AaCBF4 directly regulated AaBAM3.1 expression. In addition, the expression of both AaBAM3.1 and AaCBF4 in kiwifruit responded positively to cold stress. Hence, we conclude that the AaCBF-AaBAM module is involved in the positive regulation of the freezing tolerance of kiwifruit.